Organizational Innovation and Tech Innovation Persistence - Del Carpio, Javier Fernando (2020)
In developing economies, little is invested in research and development. Therefore, it is proposed that lower-tech firms develop their absorptive capacity and be linked through market and institutional networks to achieve technological innovation persistence. This study uses a multinomial logistics model applied to a sample of Peruvian manufacturing firms, concluding that there is an impact on product and process innovation persistence. Thus, executives can emphasize organizational innovation and absorptive capacity as means to achieve product innovation in developing countries. Moreover, firms should to prioritize the relationships with the market and institutions to achieve a better good or service.